2022
DOI: 10.1021/acs.analchem.2c03963
|View full text |Cite
|
Sign up to set email alerts
|

DNA Dendrimer-Based Directed 3D Walking Nanomachine for the Sensitive Detection and Intracellular Imaging of miRNA

Abstract: Taking advantage of the remarkable processivity and membrane penetrability, the gold nanoparticle (AuNP)-based three-dimensional (3D) DNA walking nanomachine has induced tremendous promise in molecular diagnostics and cancer therapy, whereas the executive ability of this nanomachine was eventually limited because of the disordered assembly between the walker and the track. Therefore, we developed a well-directed 3D DNA walking nanomachine by employing a DNA dendrimer as the track for intracellular imaging with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Recently, the DNA walker, a novel dynamic nanomachine, has garnered wide attention in bioimaging and sensing systems , due to its flexible function and ingenious design. At present, most of the reported DNA walkers, such as one-dimensional (1D) , and two-dimensional (2D) DNA walkers, , are faced with difficulties of the limited number and length of arms resulting in the derailment of the DNA walker, further restricting the whole reaction rate and sensing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the DNA walker, a novel dynamic nanomachine, has garnered wide attention in bioimaging and sensing systems , due to its flexible function and ingenious design. At present, most of the reported DNA walkers, such as one-dimensional (1D) , and two-dimensional (2D) DNA walkers, , are faced with difficulties of the limited number and length of arms resulting in the derailment of the DNA walker, further restricting the whole reaction rate and sensing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a powerful tool for recording and processing time-related information and has attracted a wide range of attention from researchers. Owing to its high stability, modifiability, and programmability, DNA has promising applications in biosensing [ 8 , 9 , 10 ], disease diagnosis [ 11 , 12 , 13 ], molecular computing [ 14 , 15 , 16 , 17 ], information storage [ 18 , 19 , 20 ], nanomachines [ 21 , 22 ], and quantum computing [ 23 , 24 ]. It is one of the ideal materials for constructing artificial state machines.…”
Section: Introductionmentioning
confidence: 99%
“…15−18 Wang et al proposed a well-directed threedimensional walking nanomachine based on a DNA dendrimer track for the intracellular detection and imaging of microRNA (miRNA). 19 Miao et al presented a DNA bipedal walking nanomachine for nucleic acid detection, including miRNA, circulating tumor DNA, and viral DNA/RNA. 20 These studies demonstrated the effectiveness of DNA nanomachines in nucleic acid-based detection/diagnosis following the complementary base pairing principle.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the specificity and thermodynamics of Watson–Crick base pairing rules, artificial DNA nanomachines combine the advantages of programmability, self-assembly, and predictability, and they have been applied in the smart detection/diagnosis of diseases or controllable drug release. Wang et al proposed a well-directed three-dimensional walking nanomachine based on a DNA dendrimer track for the intracellular detection and imaging of microRNA (miRNA) . Miao et al.…”
Section: Introductionmentioning
confidence: 99%